Factors associated with all-cause mortality and morbidity of motorcycle crash-related neurological and musculoskeletal injuries in Uganda: the MOTOR cluster randomised trial ancillary study - Lule, Herman; Mugerwa, Micheal; Abio, Anne; Oguttu, Benson; Kakeeto, Andrew; Asiimwe, Daniel; Lekuya, Hervé Monka; Ssebuufu, Robinson; Kyamanywa, Patrick; Bärnighausen, Till; Wilson, Michael L.; Posti, Jussi P. (BMJ, 2026)
Introduction
This study examined the factors linked to all-cause mortality and morbidity from neurological and musculoskeletal injuries during motorcycle accidents in Uganda.
Methods
The study was part of a two-armed, parallel, multi-period, cluster-randomised controlled trial of 1003 motorcycle crash victims. Morbidity was assessed using various scoring systems, and mixed effects regression models were employed for analysis.
Results
Ninety-day all-cause mortality was 9.2% (82/887). Factors associated with mortality included referral-to-dispatch >1 hour (OR 4.215 (1.802–9.858), p=0.001), Kampala Trauma Score (KTS) ≤6 (OR 7.696 (1.932–30.653), p=0.004), GCS 9–12 (OR 3.432 (1.194–9.870), p=0.022), GCS ≤8 (OR 6.919 (2.212–21.645), p=0.001), intra-axial lesions (OR 78.647 (9.871–626.587), p<0.001), extra-axial lesions (OR 11.933 (1.386–102.750), p=0.024), skull fracture (OR 11.366, (1.197–107.977), p=0.034) and craniotomy (OR 0.260 (0.095–0.706), p=0.008).
A percentage of 14.5% had unfavourable Glasgow Outcome Scale (1–3); associated factors included increasing age (OR 1.02 (1.013–1.045, p<.001), multiple injuries (OR 4.559 (1.185–17.531), p=0.027), KTS 7-8 (OR 2.755 (1.285–5.906), p=0.009), KTS ≤6 (OR 7.551 (2.815–20.255), p=0.001), GCS 9-12 (OR 4.07 (1.901–8.719), p=0.001), GCS ≤8 (OR 13.779 (5.643–33.645), p<0.001) and craniotomy (OR 0.149 (0.075–0.295), p<0.001).
Factors associated with unfavourable patient-reported musculoskeletal outcomes included being married (OR 1.984 (1.322–2.976), p=0.001), multiple injuries (OR 1.762 (1.001–3.100), p=0.049) and enrolment after the onset of the COVID-19 pandemic (OR 2.095 (1.199–3.659), p=0.009].
Conclusions
The key determinants of mortality and adverse neurological and musculoskeletal injury outcomes observed in this study are essential for establishing core outcome sets in future research and predictive models.